Menguak Misteri Harta Karun Warisan Bapak Tua Semar: Mengenal Paham Mukrominiyyah Jangga Indramayu - A. R. Idhamkholid (ISTAWA, 2017)
Poverty often leads people to kufr and leads them into a life of mirage and imagination. The phenomenon of life with this ornate fantasy seems to be found on the followers of Mukrominiyyah understanding or teachings led by Mr. Mukromin in the Jangga Village, Jangga Distric,  Indramayu. The approach used in this research is a qualitative approach. by using primary and secondary data with data collecting technique through: library research, participant observation, open interview and depth. Research conclusion 1. Genealogy Mukrominiyyah. Mukrominiyyah is a religious group that begins with the emergence of a thought named Mukromin. Mukrominiyah is located in Jangga Village, Jangga District, Indramayu. 2. Doctrine and teachings Mukrominiyyah include: Treasure, character, fiqh, Sufism and monotheism. 3. Implications of Mukrominiyyah doctrine and teachings. 1. Positive implications include: Mukrominiyyah followers who are patient, wise and generous. While the negative implications are: the followers Mukrominiyyah have the nature of the dreamer, lazy to work and disturbed his faith.